Systematic revision of Johnmannia Irwin and Lyneborg (Diptera: Therevidae): Atypical metallic stiletto flies from Australian mesic habitats - Lambkin, Christine L.; Recsei, Jacqueline M.; Yeates, David K. (Zootaxa, 2005)
The Australian endemic genus Johnmannia Irwin and Lyneborg contains unusual, large therevids with glossy black integument reflecting blues and greens. The very rarely collected Johnmannia have only been found in closed wet sclerophyll forests and rainforests, an atypical niche in the Australian environment for the Family Therevidae. The single described species of Johnmannia has only been collected from Tasmania. Here we describe two new species of Johnmannia from the Australian mainland; Johnmannia powerae Lambkin & Recsei and Johnmannia kosciuszkoensis Lambkin & Recsei. The Australasian Therevidae contains three endemic genus-groups: the Anabarhynchus Macquart genus-group, the Agapophytinae Winterton, and the Taenogera Kröber genusgroup containing Johnmannia. All three species of Johnmannia are included in a phylogenetic analysis of the Taenogera genus-group and the genus is systematically revised, with phylogenetic placement, full morphological descriptions including illustrations, specimen data, distribution maps, and detailed comparisons of male and female genitalia.